2013
DOI: 10.3344/kjp.2013.26.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Role of Catheter's Position for Final Results in Intrathecal Drug Delivery. Analysis Based on CSF Dynamics and Specific Drugs Profiles

Abstract: Intrathecal drug delivery is an effective and safe option for the treatment of chronic pathology refractory to conventional pain therapies. Typical intrathecal administered drugs are opioids, baclofen, local anesthetics and adjuvant medications. Although knowledge about mechanisms of action of intrathecal drugs are every day more clear many doubt remain respect the correct location of intrathecal catheter in order to achieve the best therapeutic result. We analyze the factors that can affect drug distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Increasing the dosage does not significantly increase the concentration at the site of action in the CSF, but instead results in high plasma levels (47,(61)(62)(63). As a result, spasticity is often not well controlled, leading to a significant loss of function with continued pain and care-related problems (64), combined with side-effects that may be intolerable (15,47). Thus, there is a need for action in patients who fail to respond adequately to oral baclofen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the dosage does not significantly increase the concentration at the site of action in the CSF, but instead results in high plasma levels (47,(61)(62)(63). As a result, spasticity is often not well controlled, leading to a significant loss of function with continued pain and care-related problems (64), combined with side-effects that may be intolerable (15,47). Thus, there is a need for action in patients who fail to respond adequately to oral baclofen.…”
Section: Discussionmentioning
confidence: 99%
“…Although widely used, baclofen is mainly water soluble and so does not readily cross the blood-brain barrier (14). As a result, patients may require a high dose to treat their spasticity effectively, which can cause intolerable side-effects (15). As an alternative, baclofen can be delivered directly to the cerebrospinal fluid (CSF) in the intrathecal space, bypassing the blood-brain barrier entirely.…”
mentioning
confidence: 99%
“…Jose et al [15] suggested that drug features, CSF dynamics, and patient characteristics should be considered when determining the location of the intrathecal catheter. In conclusion, this case report suggests that intrathecal baclofen administration provides satisfactory pain relief in CRPS patients with chronic intractable neuropathic pain not improved by an SCS.…”
Section: Discussionmentioning
confidence: 99%
“…Limited intrathecal diffusion has been proven in animal models, computer simulations and in humans using different flow-rate models similar to those delivered by programmable IDDS (16,23,24). Current guidelines recommend placing the catheter tip close to the target receptors of the spinal segment(s) associated with the dermatome of the primary pain generator (25).…”
Section: -Imaging During Surgical Implantation For Optimal Catheter Pmentioning
confidence: 99%